Enumerating the US Governmental Public Health Workforce. - Balio, Casey P.; Dockery, Nathan A.; Hogg-Graham, Rachel (American Journal of Public Health, 2025)
The article discusses the importance of enumeration of governmental public health workforce in the U.S. Topics include vital information about the workforce provided by enumeration, the changes that occurred in public health workforce enumeration throughout history, the need for occupation-specific enumeration to inform policymakers and agency leadership, and the objectives of Enumeration 2024 such as enumerating public health nurses specifically using novel data sources and approaches.